A proteção dos direitos indígenas: uma proposta estrutural para a incorporação do etnocídio no ordenamento jurídico nacional - BITAR, Murilo do Vale (Universidade Federal do Pará, 2017)
The ethnocide is one of the biggest and most serious dangers that surrounds indigenous peoples. The Brazilian law, in the constitutional level as well as in the infraconstitutional level, do not protects Indians from that danger. Inquiring this matter in the light of basic necessities and human rights, this thesis proposes the inclusion, in the Brazilian positive law system, of ethnocide as a specific crime type, seeking, in the manner, a better protection to Indians and the cultures they depend upon, physically and spiritually.